Class and class conflict in industrial society - Dahrendorf, Ralf. (London, 1959)
In every sense but one, this study is an essay even in its revised version. It is tentative, incomplete, open to criticism at many points, and, I hope, stimulating; but it is also longer than the rules of essay writing would permit. Despite its length, I wish to empha size the exploratory nature of my attempt to tackle problems of social conflict concerning total societies. By and large, recent devel opments of sociology have been characterized by two related features. Firstly, there has been a strong concern for the conditions of "equi librium" in "social systems." Stimulated by anthropological research, an image of society has gained prevalence in sociological thinking which emphasizes the elements of functional coordination, integra tion, and consensus in units of social organization. The attempt to evolve testable theories and applicable conclusions has led, secondly, to an ever-growing interest in comparatively small "social systems" such as communities, enterprises, and, above all, small groups. Both these concerns of contemporary sociological analysis are, to be sure, important, and have proved fruitful. At the same time, however, they have led many to abandon completely such other subjects of sociological analysis as did not seem to fit in with the general trend. As a result, there is today a considerable need for reorienting socio logical analysis to problems of change, conflict, and coercion in social structures, and especially in those of total societies. The interest in total societies, as well as in their historical dimension, is of course as old as sociology itself. Yet their neglect in recent decades makes a study like this one a venture into unmapped areas of inquiry-a venture which is guided not so much by the hope of comprehensive and final results as by the intention of challenging others to follow, criticize, and explore other avenues of discovery.
Keywords: Sociology .